Hepatic laceration as a life-threatening complication of umbilical venous catheterization - Gülcan, Hande; Hanta, Deniz; Törer, Birgin; Temiz, Adbülkerim; Demir, Şenay (The Turkish Journal of Pediatrics, 2011)
Umbilical venous catheterization is an intravenous infusion route for maintenance fluids, medications, blood products, and parenteral nutrition in preterm neonates. However, this procedure may be associated with several complications, such as infection, thrombosis, vessel perforation, and cardiac and hepatic injuries. Hepatic laceration is a rare but life-threatening complication of umbilical venous catheterization that is a result of direct injury through the liver parenchyma. Here, we present a preterm newborn with hepatic laceration as a rare and serious complication of umbilical venous catheterization.